PERANAN BAKAT KINESTETIK DALAM MENINGKATKAN PRESTASI BELAJAR MAHASISWA FAKULTAS SENI PERTUNJUKAN INSTITUT SENI INDONESIA DENPASAR - Sarwa, I Nengah (Universitas Pendidikan Ganesha, 2012)
In this global era, intelligence is not everything. Gardner states that human has multiple intelligences,namely: logical-mathematic intelligence, linguistic/verbal intelligence, spatial visual intelligence, bodily kinestheticintelligence, musical intelligence, social intelligence, interpersonal intelligence, spiritual intelligence,and natural intelligence. Goleman adds one more intelligence, emotional intelligence. In this context, educationis challenged to develop intelligence owned by students, so it can produce humans having life skill andcompetency in their field, so they successfully run their life.This research aimed at knowing the significant correlation and the value of contribution between bodilykinesthetic intelligence and students’ traditional music art achievement. So, it is known how far the role ofbodily kinesthetic in improving students’ learning achievement.This research was done by collecting data in the form of bodily kinesthetic intelligence score andtraditional music art achievement score with test on students of traditional music art of the fourth semester inthe academic year 2008/2009. The acquired data were then analyzed. Interpretation of data analysis was performedwith statistical method called regression and correlation tests. The data analysis discovers; (1) there isa positive and significant correlation between bodily kinesthetic intelligence and traditional music art achievement with a coefficient correlation of 0.66, (2) in improving traditional music art learning achievement, bodilykinesthetic has contribution of 44%.Keywords: instruction, bodily kinesthetic intelligence, learning achievement